Formation of Discipline Character of Students Through Hizbul Wathan (Hw) Extracurricular In MAM Talu Kecamatan Talamau Kabupaten Pasaman Barat - aditia pratama (Program Pascasarjana UMSB, 2022)
One of the important characters to be developed based on Presidential Regulation No. 87 of 2017 is the character of discipline. Discipline is an attitude or action that shows an orderly, obedient, orderly state and should be in accordance with existing regulations, provisions, and norms. The formation of disciplined character is very necessary, because discipline is the key that shows the character of modern society. One of the efforts in forming disciplinary character at Madrasah Aliyah Muhammadiyah is through Hizbul Wathan extracurricular activities. Talamau, West Pasaman Regency.This research is a qualitative research with a descriptive approach, with the aim of 1) Describing and analyzing the implementation of Hizbul Wathan (HW) extracurricular activities in the formation of student discipline characters at MAM Talu, Talamau District, West Pasaman Regency 2). Describe and analyze the material for Hizbul Wathan (HW) extracurricular activities in the formation of student discipline characters at MAM Talu, Talamau District, West Pasaman Regency 3). Describe and analyze Hizbul Wathan (HW) Extracurricular Activities Methods in Forming Student Discipline Characters at MAM Talu, Talamau District, West Pasaman Regency. The research location is in MAM Talu, Talamau District, West Pasaman Regency. The object of research, the Head of Madrasah, Deputy Head of Student Affairs, extracurricular trainer Hizbul Wathan. The instruments in this study were interview guidelines, observation guidelines and documentation. Data analysis techniques are descriptive analysis, data reduction, data presentation and draw conclusions.The results showed that 1) The implementation of Hizbul Wathan (HW) extracurricular activities in the formation of the Disciplined Character of Students at MAM Talu, Talamau District, West Pasaman Regency was carried out in three forms of activity, namely, firstly integration into subjects, secondly included in the lesson schedule with two time allocations. hours of lessons in one week and the third implementation of exercises in the field twice a week 2). Hizbul Wathan (HW) extracurricular activities in the formation of the Disciplined Character of Students at MAM Talu consist of religious material, dress code and marching material and Kemuhammadiyahan 3). Hizbul Wathan (HW) Extracurricular Activities Methods in Forming Student Discipline Characters are the lecture method, drill method, and field practice method.